1990
DOI: 10.1128/mcb.10.5.1908
|View full text |Cite
|
Sign up to set email alerts
|

Genetic exploration of interactive domains in RNA polymerase II subunits.

Abstract: The two large subunits of RNA polymerase H, RPB1 and RPB2, contain regions of extensive homology to the two large subunits of Escherichia coli RNA polymerase. These homologous regions may represent separate protein domains with unique functions. We investigated whether suppressor genetics could provide evidence for interactions between specific segments of RPB1 and RPB2 in Saccharomyces cerevisiae. A plasmid shuffle method was used to screen thoroughly for mutations in RPB2 that suppress a temperature-sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 27 publications
2
13
0
Order By: Relevance
“…Perhaps the simplest interpretation of their results and the present results is that both amino-terminal and carboxyl-terminal sequences of the largest subunit interact directly with a single region near the carboxyl terminus of the second-largest subunit. In addition, as also discussed by Martin et al (23), there remains the possibility that the genetic suppression observed in our work as well as theirs is a consequence of indirect interaction of the two regions at a distance. Therefore, their results are not necessarily in conflict with ours.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Perhaps the simplest interpretation of their results and the present results is that both amino-terminal and carboxyl-terminal sequences of the largest subunit interact directly with a single region near the carboxyl terminus of the second-largest subunit. In addition, as also discussed by Martin et al (23), there remains the possibility that the genetic suppression observed in our work as well as theirs is a consequence of indirect interaction of the two regions at a distance. Therefore, their results are not necessarily in conflict with ours.…”
Section: Discussionsupporting
confidence: 79%
“…Martin et al (23) carried out suppressor analysis to obtain information on interactions between specific segments of the largest (B220 or RPB1) and the second-largest (B150 or RPB2) subunits of S. cerevisiae RNA polymerase II. They used two temperature-sensitive mutations, one located near the carboxyl terminus of B220 (in region H) and the other located near the carboxyl terminus of B150 (in region I).…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, subunit-subunit contacts within RNA polymerase II have been suggested mainly by mutant studies with the yeast S. cerevisiae and by co-expression studies of subunits from Arabdopsis thaliana. For instance, subunit-subunit interactions have been suggested between RPB1 and RPB2 (Martin et al 1990) and between RPB1 and RPB6 (Archambault et al 1990) of S. cerevisiae RNA polymerase II; and between B36 (RPB3 homologue) and B13.6 (RPB11 homologue) of A. thaliana RNA polymerase II (Ulmasov et al 1996). An understanding of the subunit-subunit network within RNA polymerase II may be useful in making up experimental strategies for the establishment of an in vitro reconstitution system of this multisubunit complex enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely two extragenic suppressors of the GD1347 conditional-lethal substitution in interval H of the yeast 13' homolog [ Fig. 5) occur in conserved region I of yeast 13 homolog [rpb2-510(SL1145) and rpb2-513(DNl125); Martin et al 1990]. Thus, the two carboxy-terminal regions of 13 and 13' appear either to interact structurally or to affect the same mechanistic Cold Spring Harbor Laboratory Press on May 12, 2018 -Published by genesdev.cshlp.org Downloaded from step in transcription.…”
Section: Interval 5--tightly Clustered Substitutions M a Region Similmentioning
confidence: 99%